Combination of single-molecule magnet behaviour and luminescence properties in a new series of lanthanide complexes with tris(pyrazolyl)borate and oligo(β-diketonate) ligands. Issue 23 (14th May 2020) - Mikhalyova, Elena A.; Zeller, Matthias; Jasinski, Jerry P.; Butcher, Raymond J.; Carrella, Luca M.; Sedykh, Alexander E.; Gavrilenko, Konstantin S.; Smola, Sergey S.; Frasso, Michael; Cazorla, Sebastian Calderon; Perera, Kuluni; Shi, Anni; et al.
Abstract : Mono-, di- & trinuclear ternary complexes of Dy 3+ & Tb 3+ with pyrazole & oligo-diketonates are both luminescent and single molecule magnets. Quantum yields & U eff values decrease with higher nuclearity & reduced intramolecular Ln–Ln distance. Abstract : A series of tris(pyrazolyl)borate mono-, di- and trinuclear complexes, [Tp2 Ln] n X (Ln = Eu, Tb, Gd, Dy, X n − = various mono-, bis- and tris(β-diketonates) has been prepared. The Tb 3+ and Dy 3+ complexes are luminescent single molecular magnets (SMM) and exhibit luminescence quantum efficiencies up to 73% for the Tb 3+ and 4.4% for the Dy 3+ compounds. Similar Eu 3+ complexes display bright emission only at lower temperatures. The Dy 3+ and Tb 3+ complexes possess SMM behavior in a non-zero dc field at low temperatures, while the polynuclear Dy 3+ complexes also show slow magnetic relaxation even in zero dc field up to 8 K. U eff -values determined from dynamic magnetic measurements were up to 31 and 6 cm −1 for the Dy 3+ and Tb 3+ complexes, respectively. It was found that within a series of Dy 3+ and Tb 3+ compounds, U eff and luminescence quantum yields decreased with increasing nuclearity of the compounds and a shortening of the intramolecular Ln–Ln distance. Δ Orbach -values estimated from low-temperature luminescence spectra were significantly higher than those obtained from ac magnetic data, which may be due to involvement of additional processes in the relaxation mechanism (quantum tunneling, Raman, direct) reducing the energy barrier. Some of the Tb 3+ -compounds also display metal-centred electroluminescence, giving them potential as emitting layers in LEDs.